Total Surface Area of a Through-and-Through Oromandibular Defect Is Associated With Thromboembolic Events for Reconstruction With a Single Fibula Free Flap. (April 2023) - Chen, Ching-En; Ma, Chun-Yu; Wang, Tien-Hsiang; Lin, Chih-Hsun; Wu, Szu-Hsien; Perng, Cherng-Kang; Ma, Hsu; Shih, Yu-Chung
Abstract : Background: Reconstruction of through-and-through composite oromandibular defects (COMDs) has been a challenge to plastic surgeons for decades. When using a free osteoseptocutaneous fibular flap, the skin paddle is restricted by the orientation of the peroneal vessels and the inset of bone segment(s). Although the combination of double flaps for extensive COMDs is viable and reliable, the decision of single- or double-flap reconstruction is still debated, and the risk factors leading to complications and flap failure of single-flap reconstruction are less discussed. Aim and Objectives: The aim of this study was to determine objectively predictive factors for postoperative vascular complications in through-and-through COMDs reconstructed with a single fibula flap. Methods: This was a retrospective cohort study in patients who underwent single free fibular flap reconstruction for through-and-through COMDs in a tertiary medical center from 2011 to 2020. The enrolled patients' characteristics, surgical methods, thromboembolic event, flap outcomes, intensive care unit care, and total hospital length of stay were analyzed. Results: A total of 43 consecutive patients were included in this study. Patients were categorized into a group without thromboembolic events (n = 35) and a group with thromboembolic events (n = 8). The 8 subjects with thromboembolic events were failed to be salvaged. There was no significant difference in age, body mass index, smoking, hypertension, diabetes mellitus, and history of radiotherapy. The length of bony defect (6.70 ± 1.95 vs 9.04 ± 2.96, P = 0.004) and the total surface area (105.99 ± 60.33 vs 169.38 ± 41.21, P = 0.004) were the 2 factors that showed a significant difference between the groups. Total surface area was the only significant factor in univariate logistic regression for thromboembolic event ( P = 0.020; odds ratio, 1.02; 95% confidence interval [CI], 1.003–1.033) and also in multivariate logistic regression analysis after adjusting confounding factors ( P = 0.033; odds ratio, 1.026; 95% CI, 1.002–1.051). The cutoff level of total surface area in determining thromboembolic event development was 159 cm 2 ( P = 0.005; sensitivity of 75% and specificity of 82.9%; 95% CI, 0.684–0.952). Conclusions: Free fibula flap has its advantages and drawbacks on mandible restoration. Because there is a lack of indicators before, a large total surface area may be an objective reference for single-flap reconstruction of through-and-through COMDs due to an elevated risk of thromboembolic event.